VARIABILITY OF SATELLITE-OBSERVED SEA SURFACE HEIGHT IN THE TROPICAL INDIAN OCEAN: COMPARISON OF EOF AND SOM ANALYSIS - Iskandar, Iskhaq (Makara Journal of Science, 2009)
Weekly sea surface height (SSH) in the tropical Indian Ocean (20°S - 20°N) was analyzed for the period of January 1993 – December 2007 using an empirical orthogonal function (EOF) and a self-organizing maps (SOM) analysis. The EOF analysis identifies four patterns and three of them are contained in the SOM patterns. The SOM, on the other hand, characterizes the sea level variability, which shows twenty-five patterns. The patterns with low (high) sea surface height anomaly (SSHA) in the southern (northern) hemisphere associated with the monsoonal winds dominate the variation in both two methods. The SOM is also able to separate typical patterns associated with the ENSO and or the Indian Ocean Dipole (IOD) events. Low SSHA occupied the western half of the basin while high SSHA loaded in the eastern basin when the La Niña event is taking place. The El Niño event is characterized by low SSHA in the northern hemisphere, along the equator and along the eastern boundary, while high SSHA in the southwestern part of the basin. The IOD event shows a dipole like pattern with low SSHA in the east and high SSHA in the west. When the IOD co-occurred with El Niño, a distinct dipole pattern is clearly observed.